Africa?s liberation the legacy of Nyerere (Nairobi Fountain Publishers, 2010)
Julius Kambarage Nyerere, the first president of Tanzania, was a Pan-Africanist and an internationalist, and this book includes contributions from leading commentators?those who worked and fought imperialism alongside Nyerere, members of a younger generation, and Nyerere in his own words. The writings reflect on Nyerere and liberation, the Commonwealth, leadership, economic development, land, human rights, and education. Above all, they are a testament to the growing recognition of the need to rekindle the fires of African socialism to which Nyerere was deeply committed.
Includes bibliographical references and index.
Keywords: Nyerere, Julius K., 1922-1999.